Effect of caffeine on hippocampal memory and levels of gene expression in social isolation stress - Keloglan, Seval Musuroglu; Sahin, Leyla; Kocahan, Sayad; Annac, Ebru; Tirasci, Nurhan; Pekmezekmek, Ayper Boga (Wiley, 2023)
BackgroundCaffeine (Cf) antagonizes the adenosine receptors and has neuroprotective properties. The effect of Cf has been seen on stress-induced deficits of cognitive. In this study, we have investigated the effect of Cf on learning and memory functions induced by social isolation (SI) stress. Materials and methodsIn the present study, 21-day-old Wistar albino male rats (n = 28) were divided into four groups: the control (C), the SI, the Cf, and the social isolation + caffeine (SICf). Cf (0.3 g/L) was added to the drinking water of the experimental animals for 4 weeks. The learning and memory functions were assessed using the Morris Water Maze Test (MWMT). Following, was performed histopathological evaluation and determined hippocampal gene expression levels by RT-qPCR. ResultsAccording to MWMT findings, the time spent in the quadrant where the platform removed was decreased in the SI group compared with the C (p < 0.05). Histological evaluation showed morphological changes in SI by irregular appearance, cellular edema, and dark pycnotic appearance of nuclei in some neurons. However, it was observed that the histological structure of most of the neurons in the SICf group was similar to the C and Cf groups. Hippocampal SNAP25 expression was decreased in the Cf and SICf groups than in the C group (p < 0.05). The GFAP expression was increased in the SICf group than in the C group (p < 0.05). NR2A increased in the SI and SICf groups compared with C and Cf groups (p < 0.05). NR2B expression decreased in the Cf group compared with C and SI groups (p < 0.05). ConclusionsSI impaired spatial memory and causes morphological changes in adolescent rats, but this effect of isolation was not seen in Cf-treated animals. The effects of SI on NR2A, Cf on NR2B, and SNAP25 are remarkable. Here, we propose that the impaired effect of SI on spatial memory may be mediated by NR2A, but further studies are needed to explain this effect.
Keywords: adolescent rats; caffeine; hippocampus; learning and memory; social isolation